Increased Serum Trimethylamine N-Oxide Level in Type 2 Diabetic Patients with Mild Cognitive Impairment - Xu N; Wan J; Wang C; Liu J; Qian C; Tan H (Diabetes, Metabolic Syndrome and Obesity, 2022)
Nongzhang Xu,1,* Jianwei Wan,1,* Cuihong Wang,1 Jiatao Liu,2 Chenqai Qian,1 Hongyang Tan3 1Department of Pharmacy, Shanghai University of Medicine and Health Science Affiliated Zhoupu Hospital, Shanghai, People’s Republic of China; 2Department of Oncology, the First Affiliated Hospital of Anhui Medical University, Hefei, People’s Republic of China; 3Clinical Research Center for Mental Disorders, Chinese-German Institute of Mental Health Shanghai Pudong New Area Mental Health Center, School of Medicine, Tongji University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hongyang Tan, Clinical Research Center for Mental Disorders, Chinese-German Institute of Mental Health, Shanghai Pudong New Area Mental Health Center, School of Medicine, Tongji University, Shanghai, People’s Republic of China, Tel +86-18321133996, Email tanhongyang2013@163.comPurpose: Trimethylamine N-oxide (TMAO) is a metabolite of phosphatidylcholine in red meat and other diets, which is associated with cardiovascular and other diseases. The aim of this study is to evaluate the associations of serum TMAO with mild cognitive impairment (MCI) in the Chinese type 2 diabetes mellitus (T2DM) population.Materials and Methods: A total of 253 hospitalized T2DM patients and 150 healthy controls were included in this cross-sectional study. Montreal Cognitive Assessment (MoCA) assessed the cognition function, and the 253 T2DM patients were divided into 74 subjects with MCI and 179 with non-MCI. Demographic data and biochemical test results were evaluated. Serum TMAO level was measured by high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS).Results: A higher serum TMAO level was observed in T2DM patients compared with the healthy controls (P < 0.001). Among all T2DM patients, the MCI group (n = 74) showed higher serum TMAO levels than the non-MCI group. Spearman correlation test showed that TMAO levels were significantly positively correlated with age (r = 0.147, P = 0.019), body mass index (BMI) (r = 0.153, P = 0.015), diabetes duration (r = 0.160, P = 0.011), HbA1c (r = 0.138, P = 0.029), triglyceride (TG) (r = 0.138, P = 0.029), creatinine (r = 0.184, p = 0.003), hs-CRP (r = 0.243, P < 0.001), and were negatively correlated with HDL-C (r = − 0.144, P = 0.022), BDNF (r = − 0.165, p = 0.009), and MoCA (r = − 0.386, P < 0.001) score (all P < 0.05). Multivariable Logistic regression identified high serum TMAO level as a significant independent factor of MCI in the T2DM patients (OR = 1.404, 95% CI = 1.255– 1.571; P < 0.001).Conclusion: Our study showed that T2DM patients with MCI have elevated serum TMAO levels.Keywords: trimethylamine N-oxide, type 2 diabetes mellitus, mild cognitive impairment, Montreal Cognitive Assessment, healthy control